Blockchain Technology for Enhancing Supply Chain Performance and Reducing the Threats Arising from the COVID-19 Pandemic (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
A rigorous examination of the most recent advancements in blockchain technology (BCT) and artificial intelligence (AI)-enabled supply chain networks is provided in this book. The edited book brings together the perspectives of a number of authors who have presented their most recent views on blockchain technology and its applications in a variety of disciplines. The submitted papers contribute to a better understanding of how blockchain technology can improve the efficacy of human activities during a pandemic, improve traceability and visibility in the automotive supply chain, support food safety and reliability through digitalisation of the food supply chain, and increase the performance of next-generation digital supply chains, among other things. The book attempts to address and prepare a way to address the complicated issues that supply chains are encountering as a result of the global pandemic.